Teacher Educators and Trainee Teachers' Attitude toward Online Teacher Education Courses - Md. Meraz Ahmed; Md. Rokonuzzaman; Md. Kamal Hossain (Jurnal Pendidikan, 2022)
The purpose of the study was to explore the attitude toward Online Teacher Education Courses (OTECs). To that end, this study was carried out over the teacher educators and trainee teachers of Bangladesh Open University. Here, teacher educators represent the faculty members of the School of Education (SoE) of Bangladesh Open University (BOU), and trainee teachers represent the Master of Education (M.Ed.) and Bachelor of Education (B.Ed.) students of BOU. A mixed research approach with triangulation was used to conduct the study with a descriptive survey, two Focus Group Discussions (FGDs), and one key personnel interview. Data were collected from a total of 602 teacher trainees (182 were M.Ed. students and 420 were B.Ed. students) and 12 teacher educators, selected through multiple sampling techniques. The  data revealed that the teacher educators and trainee teachers had a positive attitude towards online courses since the mean score of faculty members, M.Ed., and B.Ed. students of BOU were 3.60, 381, and 3.81, respectively. Considering all these aspects, this study suggested that SoE/BOU needs to decide rationally to shape its future Online Teacher Education Courses (OTECs). This research contributes to the basement of new knowledge through an explorative study with all the possible stakeholders covering the whole country of interest.